2015
DOI: 10.1002/cncr.29439
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of levetiracetam in patients treated with concomitant chemoradiotherapy and adjuvant chemotherapy with temozolomide for glioblastoma multiforme

Abstract: BACKGROUND: A chemosensitizing effect of levetiracetam (LEV) has been suggested because LEV inhibits O-6 methylguanine-DNA methyltransferase (MGMT). However, the survival benefit of LEV has not been clinically documented. The objective of this study was to assess the survival benefit of LEV compared with other antiepileptic drugs as a chemosensitizer to temozolomide for patients with glioblastoma. METHODS: In total, 103 consecutive patients with primary glioblastoma who received concomitant chemoradiotherapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 21 publications
2
48
2
Order By: Relevance
“…For this reason a possible intrinsic antineoplastic effect of these drugs would be useful. In addition to the anticonvulsant mechanism, some AED have been previously described to exert a cytotoxic effect that, added to the effects of conventional chemo-radiotherapy, possibly impacts also on the survival of these patients [10, 16, 17]. Our results show that BRV and LCM in vitro exert a dose-dependent cytotoxic effect on various glioma cell lines and this effect was concomitant with the modulation of a number of miRNAs.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…For this reason a possible intrinsic antineoplastic effect of these drugs would be useful. In addition to the anticonvulsant mechanism, some AED have been previously described to exert a cytotoxic effect that, added to the effects of conventional chemo-radiotherapy, possibly impacts also on the survival of these patients [10, 16, 17]. Our results show that BRV and LCM in vitro exert a dose-dependent cytotoxic effect on various glioma cell lines and this effect was concomitant with the modulation of a number of miRNAs.…”
Section: Discussionsupporting
confidence: 56%
“…Bobustuc and colleagues reported that levetiracetam inhibited in vitro human glioma cell proliferation through p53-mediated MGMT inhibition, thus increasing glioma cell sensitivity to temozolomide [10]. Moreover, in a recent clinical study, Kim and colleagues showed that patients with glioblastoma receiving temozolomide-based chemotherapy and levetiracetam for seizure control, experienced a significant survival benefits [16]. Our in vitro data suggest that some characteristics of the parent drug levetiracetam might be shared by BRV, however further study is needed to verify the effect of BRV on MGMT expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a single institutional retrospective study, Kim et al 23 noticed that the median progression-free survival (PFS) and OS for patients who received LEV in combination with TMZ was significantly prolonged compared to those who did not receive LEV (PFS 9.4 vs 6.7 months, p=0.010; OS 25.7 vs 16.7 months, p=0.027).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on the impact of different AEDs on GBM survival [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Previous research reports that valproate use improves survival in GBM patients [11,12,[17][18][19].…”
Section: Statistical Analysesmentioning
confidence: 99%